Cost of survivorship care and adherence to screening—aligning the priorities of health care systems and survivors. Issue 1 (7th January 2020) - Benedict, Catherine; Wang, Jason; Reppucci, Marina; Schleien, Charles L; Fish, Jonathan D
Abstract : Survivors of childhood cancer are less adherent to screening recommendations as the cost of screening increases. This finding aligns the interests of the survivors (better adherence) with that of the health system (higher reimbursement). Abstract: Childhood cancer survivors (CCS) experience significant morbidity due to treatment- related late effects and benefit from late-effects surveillance. Adherence to screening recommendations is suboptimal. Survivorship care programs often struggle with resource limitations and may benefit from understanding institution-level financial outcomes associated with patient adherence to justify programmatic development and growth. The purpose of this study is to examine how CCS adherence to screening recommendations relates to the cost of care, insurance status, and institution-level financial outcomes. A retrospective chart review of 286 patients, followed in a structured survivorship program, assessed adherence to the Children's Oncology Group follow-up guidelines by comparing recommended versus performed screening procedures for each patient. Procedure cost estimates were based on insurance status. Institutional profit margins and profit opportunity loss were calculated. Bivariate statistics tested adherent versus nonadherent subgroup differences on cost variables. A generalized linear model predicted the likelihood of adherence based on cost of recommended procedures, controlling for age, gender, race, and insurance. Adherence to recommended surveillance procedures was 50.2%. Nonadherence was associated with higher costs of recommended screening procedures compared to the adherent group estimates ($2, 469.84 vs. $1, 211.44). Failure to perform the recommended tests resulted in no difference in reimbursement to the health system between groups ($1, 249.63 vs. $1, 211.08). For the nonadherent group, this represented $1, 055.13 in "lost profit opportunity" per visit for patients, which totaled $311, 850 in lost profit opportunity due to nonadherence in this subgroup. In the final model, nonadherence was related to higher cost of recommended procedures ( p < .0001), older age at visit ( p = .04), Black race ( p = .02), and government-sponsored insurance ( p = .03). Understanding institutional financial outcomes related to patient adherence may help inform survivorship care programs and resource allocation. Potential financial burden to patients associated with complex care recommendations is also warranted.